Biogeochemical Distinctiveness of Peatland Ponds, Thermokarst Waterbodies, and Lakes. Issue 11 (3rd June 2022) - Arsenault, Julien; Talbot, Julie; Brown, Lee E.; Holden, Joseph; Martinez‐Cruz, Karla; Sepulveda‐Jauregui, Armando; Swindles, Graeme T.; Wauthy, Maxime; Lapierre, Jean‐François
Abstract: Small lentic freshwater ecosystems play a disproportionate role in global biogeochemical cycles by processing large amounts of carbon (C), nitrogen (N), and phosphorus (P), but it is unlikely that they behave as one homogenous group for the purpose of extrapolation. Here, we synthesize biogeochemical data from >12, 000 geographically distinct freshwater systems: lakes, peatland ponds, and thermokarst waterbodies. We show that peatland ponds are biogeochemically distinct from the more widely studied lake systems, while thermokarst waterbodies share characteristics with peatland ponds, lakes, or both. For any given size or depth, peatland ponds tend to have dissolved organic carbon concentrations several‐fold higher and are 100‐fold more acidic than lakes because of the organic matter‐rich settings in which they develop. The biogeochemical distinctiveness of freshwater ecosystems highlights the need to account for the fundamental differences in sources and processing of organic matter to understand and predict their role in global biogeochemical cycles. Plain Language Summary: Small freshwater bodies are major (but under‐studied) contributors to the global cycling of carbon and nutrients. A large number of these ecosystems develop in climate‐sensitive organic soils. Using a dataset of >12, 000 geographically distinct freshwater bodies, we show that many of these ecosystems, namely peatland ponds and some waterbodies developing in permafrost, are structurally and functionally different than their more widely studied lake counterparts. Peatland ponds have distinct combinations of pH, nutrients, and organic carbon concentrations compared to lakes, and they are commonly much more acidic and richer in organic carbon for any given size or depth. Biogeochemically, permafrost waterbodies behave either as peatland ponds, as lakes, or as a combination of both. Our results emphasize the need to consider the distinction between peatland ponds, permafrost waterbodies, and lakes to better understand and forecast the role of small freshwater ecosystems in global biogeochemical cycles. Key Points: Peatland ponds are distinct from lakes; thermokarst waterbodies behave either like peatland ponds or lakes, or are a combination of both The distinctiveness of peatland ponds and some thermokarst waterbodies is due to their setting in climate‐sensitive organic soils The biogeochemistry of a large portion of the world's freshwater ecosystems should not be predicted using current lake‐based models and data